AN ANALYSIS OF THE TRANSLATION OF PROCEDURE TEXT IN ANDROID, IOS, WINDOWS OPERATING SYSTEMS MOBILE PHONES’ MANUAL BOOKS - Wahyu Tri Kustanti; Farida Agoes (Jurnal Bahasa Inggris Terapan, 2017)
The main objective of this research is  to find out the translation technique mostly used in translating the same words and phrases of Android, iOS and Windows mobile phones’ manual books. Its data were obtained through collecting the printed manual books and unprinted manual books from internet. The data were analyzed by using theory of translation technique by Molina & Albir (2002). The final results of the research indicate the following. First, there are 100 similar words and phrases were found among translation of 3 OS mobile phones’ manual books. Second, there are 9 translation techniques used; adaptation, amplification, borrowing, calque, establish equivalent, discursive creation, generalization, and particularization. In addition, the translation technique mostly used in translation of Android, iOS And Windows mobile phones’ manual books is Calque. Key words: Translation, Similar Words, Phrases & Sentences, Mobile Phones’ Manual Book